Availability of results from clinical research: Failing policy efforts - Shamliyan, Tatyana A.; Kane, Robert L. (Journal of epidemiology and global health, 2014)
Trial registration has a great potential to increase research transparency and public access to research results. This study examined the availability of results either in journal publications or in the trial registry from all studies registered at ClinicalTrials.gov. All 137,612 records from ClinicalTrials.gov in December 2012 were merged with all 19,158 PubMed records containing registration numbers in the indexing field or in the abstracts. A multivariate analysis was conducted to examine the association between the availability of the results with study and participant characteristics available in registration records. Fewer than 10% of the registered studies and 15% of the registered and completed studies had published results. The highest publication rate of 22.4% was for randomized trials completed between 2005 (starting year for structured indexing in PubMed of study registration) and 2010. For 86% of overall and 78% of completed registered studies, no results were available in ClinicalTrials.gov or in journal publications. Studies funded by industry vs. other funding sources and drug studies vs. all studies of other interventions were published less often after adjustment for study type, subject characteristics, or posting of results in ClinicalTrials.gov. Existing policy does not ensure availability of results from clinical research. International policy revisions should charge principal investigators with ensuring that the approved protocols and posted data elements are aligned and that results are available from all conducted studies.